(untitled) - Iregren, Anders (SJWEH Supplements, 2006)
This issue of SJWEH Supplements contains nine peer-reviewed papers based on presentations made at the 51st ”Nordiska Arbetsmiljömötet” (NAM, Nordic Conference on the Work Environment) held in Erikslund, Sweden, on 28-31 August 2005. The NAM conference is organized annually with the aims of (i) providing a forum for exchanging practical experience and recent applications within work environmental research in the Nordic countries, (ii) stimulating contacts between researchers, practitioners, and also employees from governmental institutions that regulate the work environment, and (iii) publishing peer-reviewed proceedings to disseminate information from the conference to a wider audience. The first two aims were fulfilled during the conference, by the presentation of more than 50 contributions in the form of invited lectures, free oral presentations, and posters. The conference started with a special session called “Research Regulation: Legal and Ethical Aspects” with invited speakers from Norway, Denmark, and Sweden. The first paper of this supplement by Simonsen & Nylenna, “Basic Ethical, Professional and Legal Principles of Biomedical Research” represents this session. Another special session of the conference was dedicated to cortisol in saliva as a useful tool for workplace studies. This session is represented by the following four papers: “The Cortisol Awakening Response—an Exploration of Intraindividual Stability and Negative Responses” by Carlsson Eek et al, “Diurnal Profiles of Salivary Cortisol on Workdays among Construction Workers Versus White-Collar Workers” by Hansen et al, “Diurnal Cortisol Pattern of Shift Workers on a Workday and a Day Off” by Karlson et al, and “Weekday and Weekend Patterns of Diurnal Cortisol, Activation and Fatigue among People Scoring High for Burnout” by Söderström et al. The two papers that follow the four on cortisol in saliva deal with aspects of reported symptoms. They are entitled “Self-reported Conceptions of Memory and Concentration in Comparison with the Neuropsychological Test Performance of Manual Workers” by Bast-Pettersen and “Indoor-air-related Complaints and Symptoms among Hospital Workers” by Hellgren & Reijula. The last two papers, on medical problems among the workforce, are entitled “Ischemic Heart Disease and Welding in Scandinavian Studies” by Sjögren et al and “Effect of Industrial Solvent Exposure on Blood Pressure and Liver Ultrasound Echogenicity” by Kaukiainen et al. Hopefully, these eight original papers and one review will be appreciated by the readers of this issue of SJWEH supplements! The conference was concluded with a session discussing the future of NAM meetings. Representatives of the national research institutes of the participating countries presented the views of each institute, and these presentations were followed by a vivid discussion. This discussion is still continuing, and, so far, it has resulted in several proposed changes in the format of future meetings. The most important changes involve the conference being combined with some of the courses held by the Nordic Institute for Advanced Training in Occupational Health (NIVA), the official language of the conference becoming English, and a larger part of the conference being devoted to coherent themes and less time being given to free presentations. For further information on future meetings please refer to the website of the Danish institute, www.ami.dk. Many people and institutions contributed to the 51st NAM conference and to the publication of these proceedings. I am especially grateful to the members of the Nordic Program Committee in 2005, which, apart from myself, was comprised of Vidir Kristjansson, Reykjavik, Thomas Schneider, Copenhagen, Knut Skyberg, Oslo, and Helena Taskinen, Helsinki, for their contributions to the planning of the conference, as well as to the editorial process. Many others were also involved, and I wish to extend my deepest appreciation and sincere thanks to them all! Important financial support was provided by the Nordic Council of Ministers, both for the conference and for the publication of these proceedings.
Keywords: preface